Biofilm Formation in Staphylococcus aureus and Coagulase-Negative Staphylococcus - Marta Setiabudy; Dewa Ayu Putri Sri Masyeni; Anak Agung Gede Indraningrat; Kadek Suryawan; I Ketut Agus Indra Adhiputra; Muhammad Amirul bin Abdul Rahman (Folia Medica Indonesiana, 2023)
Highlights: